Pengaruh Pengukuran Kinerja Terhadap Komitmen Organisasi Melalui Keadilan dalam Prosedur Evaluasi dan Kepuasan Kerja Sebagai Variabel Mediasi - Rivaldo Maubi Ahmad; Andy Dwi Bayu Bawono (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the elements that affect organizational commitment. The research model consists of one independent variable namely performance measurement and two mediating variables namely procedureral fairness and job satisfaction. The aforementioned variables are used to determine their influence on organizational commitment as dependent variable. This research uses quantitative research and the sample is taken by using purposive sampling method from the employees of the Sharia State Savings Bank in Central Java. The sample criterias are the employee who have 1 year of job experience and have positions as manager or supervisor. This research obtained 50 data from samples by using online distribution questionnaire. Path analysis, t test and sobel test to test the effect of the mediating variables. The result shows that performance measurement has no influence on organizational commitment and the performance measurement has a significant effect on procedural justice. Further, procedural justice has also no significant effect on organizational commitment and performance measurement has a significant influence on job satisfaction. In contrary, job satisfaction has a significant effect on organizational commitment. In the mediating variable analysis, performance measurement has a direct effect on organizational commitment through procedural justice. However, performance measurement has an indirect effect on organizational commitment through job satisfaction.